Gunnar Myrdal and Asian Drama in context - Ravi Kanbur (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper attempts to understand Asian Drama in the context of the development debates of its time, and in terms of the sensibilities that Gunnar Myrdal - the brilliant economic theorist and philosopher of knowledge, and Swedish politician - brought to the conceptualization of the problems and prospects of development. The paper covers: (1) what Gunnar Myrdal brought to the analysis of development from his long, varied, and distinguished academic and practitioner career; (2) the development terrain in the mid-twentieth century; and (3) how Asian Drama lay on that terrain and in the remaining years of Gunnar Myrdal's continued eventful life. The two central questions posed in the paper are: (1) How did Gunnar Myrdal's broad experience and perspective influence Asian Drama? (2) How did Asian Drama influence the development debate?
Keywords: B31; B41; O10; O53; 330; Asian Drama; beyond economics; Gunnar Myrdal; states and elites; value judgements